Urban fruit bats give birth earlier in the season compared to rural fruit bats - Maya Weinberg; Dean Zigdon; Mor Taub; Lee Harten; Ofri Eitan; Adi Rachum; Reut Assa; Omri Gal; Yossi Yovel (BMC Biology, 2025)
Abstract Background Urbanization is rapidly altering our ecosystem. While most wild species refrain from entering urban habitats, some flourish in cities and adapt to the new opportunities these offer. Urban individuals of various species have been shown to differ in physiology, morphology, and behavior compared to their rural counterparts. While several studies have suggested that urban dwelling alters the reproductive cycle in birds, such evidence currently has not been shown for mammals. Egyptian fruit bats are highly flexible mammals that roost and forage in both urban and rural habitats. Urban-dwelling fruit bats encounter higher average temperatures and a richer supply of food (mainly fruit) during winter. Results Here, we set out to determine whether urban-dwelling fruit bats take advantage of urbanization and reproduce earlier in the annual cycle than rural fruit bats. We sampled ten fruit bat colonies located in different urbanization levels, over 3 years. We monitored the bats’ reproductive state and the size of the pups following parturition. Indeed, we found that urban fruit bats gave birth ~ 2.5 weeks earlier in spring than rural fruit bats. We also found that roosting in urban colonies did not decrease the bats’ reproductive success, in contrast to what has been suggested for some urban birds. Conclusions Our study provides new insights into the adaptation to urban living and its exploitation by one of the most common mammalian groups found in cities worldwide—bats.